Redesign of radiotherapy for prostate cancer: a proposal for universal healthcare systems - Ana Paula Beck da Silva Etges; Luciana Rodrigues de Lara; Stella Lisboa Sapper; Stella Lisboa Sapper; Ana Von Frankenberg Berger; Melissa Streck; Laise Zardo; Armani Linhares; Marina Nassif; Angelica Zanotto; Marta Nassif Pereira Lima; Rafael Vargas; et al. (Becaris Publishing Limited, 2023)
Aim: This study was designed to recommend strategies to improve prostate patients' access to radiotherapy treatment in the Brazilian Unified Health System, along with a cost-tool to support radiotherapy care pathways' lead times and costs. Methods: Data was collected prospectively from patients with prostate cancer receiving radiotherapy in two Brazilian centers to provide data to apply design thinking and process reengineering techniques. The current status of the radiotherapy pathway was determined and the length of time taken for in-hospital activities was measured using data exported from ARIA R . Interviews with patients were used to estimate their waiting periods. This provided the data used to provide recommended strategies and the cost tool based on time-driven activity-based costing. The strategies were classified according to priority. Results: Data from 47 patients were analyzed. The mean interval from diagnosis to start of radiotherapy was 349 days (SD581), and the mean interval from seeking medical attention to starting treatment was 635 days (SD629). Twelve strategies affecting in hospital processes and 11 impacting patients' care pathways and experiences are recommended, mostly focused on system improvement opportunities. A time-driven activity-based costing monitoring using data extracted from ARIA was coded and can be used by centers as a cost assessment guide. Conclusion: This study uses reengineering and design techniques to introduce priority strategies to allow more efficient and patient-centered radiotherapy.